FACTORS INFLUENCING MEMBERSHIP OF FARMERS’ IN COOPERATIVE SOCIETIES IN ABIA STATE, NIGERIA - Godwin Ndubuisi Ikechukwu MBAGWU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study analyzed factors influencing membership of farmer’s in cooperative societies in Abia State, Nigeria. Simple random sampling technique was used to select 80 co-operators. Data were collected with structured questionnaire and analyzed with descriptive statistics such as: frequency counts, mean scores and percentages and inferential statistics (probit regression analysis). The result of socio-economic characteristics of showed the farmers had mean ages of 40.67 years, household size of 4.1 persons, mean farm income of ₦201, 000.00 with a mean farming experience 6.1years. The result revealed that 57.2% and 41.2 of the farmers belonged to farmers’ multipurpose and agricultural cooperative societies. The result of probit regression estimates showed that coefficients age, farming experience, income, household size and poverty level influenced cooperative membership in the study area. Policies aimed at reducing household sizes by appropriate family planning techniques in order to reduce poverty and encouraging farmers to join cooperative societies for ease access of inputs and credit for enhanced productivity were advocated.